Msi1 inhibits cervical cancer cell apoptosis by downregulating BAK through AKT signaling - Liu, Xian (J Cancer, 2021)
Musashi-1 (Msi1) is an RNA binding protein that functions as a regulator in multiple carcinomas. Our previous study demonstrated that Msi1 could promote the proliferation of cervical cancer cells by targeting the cell cycle proteins P21, P27 and P53. However, the mechanisms by which Msi1 affects the survival of cervical cancer cells, such as apoptosis, are still unclear. In this study, we found that the expression of Msi1 inhibited cervical cancer cell apoptosis in vitro and in vivo. Furthermore, the expression of Msi1 downregulated the expression of PTEN, while AKT signaling was activated, which resulted in a reduction in the proapoptotic protein BAK. In addition, rescue the expression of BAK in Msi1 expressing cervical cancer cells induced the increase of apoptosis cells. These findings indicate that Msi1 regulates cervical cancer cell apoptosis by inhibiting PTEN and activating AKT signaling, which leads to the downregulation of BAK.